Histochemical analysis of glycoconjugate secretion in the alimentary tract of Anguilla anguilla L. - C. Domeneghini; S. Arrighi; G. Bosi; G. Radaelli; A. Veggetti (Acta Histochemica, 2005)
Conventional histochemical methods as well as lectin-binding techniques were used to study glycoconjugates that are present in the alimentary canal. of the European eel (Anguilla anguilla). Specimens from pharynx, oesophagus, stomach and intestine were collected from adult ("silver eel" stage) females. Alcian Blue pH 2.5/PAS and High Iron Diamine/Alcian Blue pH 2.5 reactions were performed to stain neutral and acidic glycoconjugates. In addition, lectin histochemistry was applied to identify acidic glycoconjugates containing O-acytated sialic acids. Finally, the presence of sugar residues in the oligosaccharide side chains of glycoconjugates were investigated by using biotinylated lectins. Acidic and neutral glycoconjugates were found to be secreted throughout the alimentary canal, the acidic glycoconjugates appeared to be either siatylated or sulphated. Sialylated glycoconjugates were identified to contain siatic acid substituted at carbon in position 7 (C7). Sulphated glycoconjugates were particularly abundant in the distal intestine and were not present in the secretory products of the gastric mucosa, which contained a variety of sugar residues (D-N-acetyl-galactosamine, beta-D-galactose, alpha-D-mannose, alpha-L-fucose, D-N-acetyl-glucosamine). Lectin binding was observed in mucous cells of pharynx, oesophagus and intestine, and particularly some monosaccharides (D-N-acetyl-galactosamine and beta-D-galactose) were abundantly present.